Study of State Land Potential Managed by UPN "Veteran" Jawa Timur Using Spatial Interpolation, Scoring, and Weight Overlay Methods - Siswanto; Purnomo Edi Sasongko (Nusantara Science and Technology Proceedings, 2023)
UPN "Veteran" Jawa Timur has 13.5 hectares of land in Wonosalam District. This land has not been used optimally to support learning, research, and community service. The problems currently faced are 1) legal land ownership boundaries are still biased, 2) site plans for land use are not yet available, and 3) land potential data is needed that can be used as a reference for land use. Based on the problems above, this research aims to map land potential based on soil characteristics using the "Spatial Interpolation, Scoring, and Weight Overlay" method. Spatial interpolation is a way of calculating representative areas from several measurement points while scoring is giving parameter values based on their potential, while "Weight Overlay" is a facility provided by ArcMap GIS that combines input spatial data with a weighting (weight factor) of the magnitude of the influence. Land map units (LMU) are obtained from overlaying relief, geology, slope, and land use maps. The results of spatial interpolation, scoring, and weight overlay for eight soil characteristics for agriculture are in a good category, 49.7% (65,610.81 m2); medium 48.82% (64,093.76 m2); bad 1.21% (1,593.09 m2). For physical buildings in the good category 16.61% (44,130.38 m2); moderate 25.66% (67,382.75 m2) and poor 7.523% (19,784.88 m2). And for tourism in the good category 22.36% (29,361.61 m2); moderate 58.10% (76,281.01 m2) and poor 19.54% (25,655.05 m2). Directions for potential agricultural use of 8,802.9 m2 (6.7%), physical buildings = 17,595.8 m2 (13.4%), and tourism = 28,890.8 m2 (22.0%), and can potentially be developed by combining agriculture and tourism = 36,890.3 m2 (28 .1%), Development of physical buildings or tourism = 39,117.9 m2 (29.79%), and all potential and development area is in Slightly Flat topography (Slope, 0-3%) to hilly (Slope, 15-25%).